Zero-Point Energy: Capturing Evanescence - Moddel, Garret (Journal of Scientific Exploration, 2022)
In results from thousands of trials and dozens of variations, tests for measurement artifacts, and replications, metal/insulator/metal/Casimir cavity devices produce electric power, apparently by tapping ambient zero-point energy (ZPE). A simple calculation shows that the power potentially available from the ZPE quantum vacuum is an immense 5 gigawatts per square meter. The devices tap a tiny fraction of that, but still deliver a practical power density of 70 watts per square meter. The devices are designed to circumvent the apparent impediments to ZPE harvesting, i.e., that ZPE is the universal ground state, and that ZPE fluctuations are extremely short lived and virtual. If the source ultimately proves to be ZPE, what is the operating principle behind the energy harvesting, and how can the results be reconciled with known physical law? A notional operating principle can be understood as a direct analog to the optical phenomenon of frustrated total internal reflection. Tapping ZPE does not violate the second law of thermodynamics based on the conventional quantum interpretation of ZPE, but ambiguities regarding the source of ZPE leave the issue unresolved.